A study on employing ted talks as a digital tool for developing communicative skills of tertiary level esl learners - Jayarathna, D.; Gamage, C. (University of Jaffna, 2022)
Purpose: TED Talks is a digital toolto promote the communicative skills of learners in a language classroom. Hence, this study aims to examine the effect of adopting TED Talks in developing speaking skills of ESL learners at the Faculty of Management and Finance, University of Ruhuna and the learners' perceptions of the efficacy of using TED Talks as a learning tool. Methodology: This action research adopts a qualitative approach where teacher journals and 20 semi-structured interviews were utilised as data collection tools. The sample includes 120 intermediate-level first-year undergraduates while the intervention was conducted for two weeks via the Zoom online platform comprising six hours each week. In each lesson, TED Talk videos were used in the pre-task, while-task and post-task activities. Thus, six TED Talk videos on debatable topics such as business, modern technology, gender equality, language learning and leadership were used with the aim of improving students' interaction in speaking activities while the teacher played the role of the facilitator. Findings: The Findings of the study suggest that boosting confidence and participation, intensifying motivation and promoting learner engagement are the key impacts of using TED Talk videos in language learning for the tertiary level ESL learners. Research limitation: A limitation in the present study was in the utilization of semi structured interviews that might produce partial views. Moreover, these results and conclusions are limited to a particular faculty in one university. Hence, these limitations might affect the possibility of generalizing the research results. Implications:In terms of the theoretical implications, the current study is significant to the field due to the absence of previous studies about incorporating TED Talks to teach speaking skills to the tertiary level ESL learners at the Faculty of Management and Finance, University of Ruhuna. As practical implications, teachers should consider the significance of using TED Talk videos in the teaching-learning process as it has an unlimited impact on the students' academic improvement. Besides, teachers should always search for innovative and enthusiastic procedures of teaching, especially in teaching English speaking to attract the students' attention and motivation to learn. In conclusion, the study serves ESL teachers at the tertiary level by adopting an innovative tool such as TED Talks in teaching language skills to solve existing issues in the teaching sphere in Sri Lanka.
Keywords: ESL learners; Language learning; Speaking skills; TED talk videos